Estudo da sensibilidade barorreflexa e sua relação com a produção de citocinas inflamatórias no processo de envelhecimento - Milan, Juliana Cristina (2014)
Aging causes changes in several human subsystems such as the cardiovascular and immune systems. The objective of this study was to evaluate the relationship between baroreflex function through linear algorithm (cross-spectral analysis) and proinflammatory cytokines in the aging process and also assess the baroreflex sensitivity, TNF-α, IL-6 and hsCRP in different ages and in the aging process. One hundred and ten apparently healthy subjects divided into 5 groups with 22 individuals each, according to age were evaluated: 21-30 years, 30-40 years, 40-50 years, 50-60 years, 60-70 years. The experimental protocol consisted of a blood samples collection for analysis of inflammatory markers and in the same day were collected ECG, blood pressure and respiratory movements for 15 minutes in the supine position and in standing position, after the active postural change for 15 minutes. For the analysis of baroreflex sensitivity cross spectral analysis (coherence, phase and gain) was used and ELISA method for analysis of TNF-α and IL-6 was used. Data were analyzed using analysis of variance one-way ANOVA test with Tukey test post-hoc or Kruskal-Wallis oneway ANOVA with Dunn's post-hoc according to the normality of the data and the Spearman correlation test. The level of significance for the tests was 5%. The main results were: 1) reduced baroreflex sensitivity during the aging process; 2) increased levels of inflammatory markers in the aging process; 3) negative correlation between IL-6 and BF gain and phase; 4) negative relationship between hsCRP and coherence, phase and gain in BF. It can be concluded that the human natural aging causes a loss of baroreflex sensitivity and increased serum levels of inflammatory markers studied, although the decrease in baroreflex sensitivity as function of the decreasing of vagal autonomic function occurred in the 41-50 age range, and only in the next age was observed changes in inflammatory markers.